## Filters

Clear All

G Gautam harsolia
We know that  cos 3x = 4 - 3cos x we use this in our problem we can write cos 6x as cos 3(2x)         cos 3(2x) = 4 - 3 cos 2x                          =    -                                                                                                                   =                                            = 32 - 4 - 48 + 24  -                           =   32  - 48 + 18 - 1  = R.H.S.

G Gautam harsolia
We know that                    We use this in our problem   cos 4x = cos 2(2x)             =                =                                                      =  = R.H.S.

G Gautam harsolia
We know that       and we can write tan 4x = tan 2(2x) So,       =                                                              =                                                      =                                                       =           = R.H.S.

G Gautam harsolia
cot x cot2x - cot3x(cot2x - cotx) Now we can write cot3x = cot(2x + x) and we know that  So,                                 =   cotx cot2x - (cot2xcotx -1)            =  cotx cot2x - cot2xcotx +1             = 1  = R.H.S.

S seema garhwal
all functions are positive in this range  We know that                         = 1 -      =    =           cos x =                  (cos x is -ve in II quadrant) We know that        cosx =                                                                       (because all functions are posititve in given range)                 similarly,                   cos x =               ...

S seema garhwal
We know that      cos x  =                  cos x + 1                                 =     + 1   =     =                                          Now,       we know that   cos x =                                         =  1 -    =    =                                        Because    is +ve in given quadrant

S seema garhwal
tan x =  We know that ,                                            =     =  x lies in II quadrant  thats why sec x is -ve  So,   Now,    =   We know that,                                                                                                    (  )                                                 =      =                                                                = ...

S seema garhwal
We know that                  we use these identities                                                                                                                           sin2x +   =   2sinx cosx  +    take 2 sinx common                                                                                                                                                             ...

S seema garhwal
We know that                  and               We use these two identities in our problem         sin7x + sin5x  =      =                          sin 9x + sin 3x =   =            cos 7x + cos5x =    =           cos 9x + cos3x =   =               =                                                                                                   =            = R.H.S.         ...

S seema garhwal
we know that                        We use this identity in our problem If we notice we need sin4x in our final result so it is better if we made a combination of sin7x and sin x , sin3x and  sin5x tp get sin4x                                                                                   take 2sin4x common                                                        = 2sin4x(cos3x +...

S seema garhwal
We know that                           and                           We use these two in our problem       and   =  +                                                                      = 1 - 2cosxcosy + 1 - 2sinxsiny                                                                                              = 2 - 2(cosxcosy + sinxsiny)                                              ...

S seema garhwal
We know that                           and                           We use these two in our problem       and   =  +                                                                      = 1 + 2cosxcosy + 1 - 2sinxsiny                                                                                              = 2 + 2(cosxcosy - sinxsiny)                                              ...

S seema garhwal
We know that                       and          We use this in our problem        =    +     =   (4sinx - 4)sinx + (4 - 4cos x)cosx   now take the 4sinx common from 1st term and  -4cosx from 2nd term =  4(1 - )  - 4(1 - ) = 4 - 4                                                                                             = 0 = R.H.S.

G Gautam harsolia
We know that  cos A+ cos B =   we use this in our problem                               (   we know that          cos(-x) = cos x ) again use the above identity we know that     = 0 So,               = 0  = R.H.S.

S seema garhwal
We know that                        We use this identity in our problem                        Now our problem simplifeis to                             = 0 take sin3x common                             So, either              sin3x = 0                                or                                                                                                                    ...

S seema garhwal
We know that  So,                  either       tan2x = 0             or                     tan2x = -1                                                  (      )             2x =                                                                   Where n  Z
sin2x + cosx = 0 We know that  sin2x = 2sinxcosx So,  2sinxcosx + cosx = 0 cosx(2sinx + 1) = 0 So, we can say that either  cosx = 0                                       or                           2sinx + 1 = 0                                                                                                                                                                Therefore, the...
We know that  We use these identities (cos3x + cosx) - cos2x = 2cos2xcosx -cos2x = 0                                      = cos2x(2cosx-1) = 0 So, either   cos2x = 0                        or                                                                                                                                               the general solution is
cos4x = cos2x cos4x - cos2x = 0 We know that We use this identity   cos 4x - cos 2x  = -2sin3xsinx  -2sin3xsinx = 0       sin3xsinx=0 So, by this we can that either  sin3x = 0     or    sinx = 0 3x =                  x =    x =                 x =   Therefore, the general solution is